Assessing and treating suicidal thinking and behaviors in children and adolescents : a play therapy guide for mental health professionals in clinical and school-based settings - Baker, Leslie W.; Cross, Mary Ruth (New York, NY : Routledge, 2024)
"Assessing and Treating Suicidal Thinking and Behaviors in Children and Adolescents is a guide to working with children and young people who present with either obvious or hidden suicidal thoughts, preoccupations, or plans. Chapters explore a range of treatment approaches and focus on how to support parents, caregivers, families, and schools. Expressive therapies are highlighted, but the chapters also cover evidence-based models such as cognitive-behavioral therapy (CBT), dialectical behavior therapy (DBT), and prescriptive play therapy. Expressive therapists, school-based counselors, and other clinicians who work with at-risk children and adolescents from diverse communities and backgrounds will come away from this book with the tools they need to integrate an individual child's capabilities, sources of distress, and internal and external resources in order to build a developmentally sensitive treatment plan"--
Understanding youth suicide -- Introduction / Mary Ruth Cross and Leslie Baker -- Law and ethics, research, media, and looking forward toward zero suicide / Leslie Baker and Mary Ruth Cross -- Integrating psychiatry into treatment of suicidal youth: information for clinicians / Daniel Kostalnick.
Keywords: Children -- Suicidal behavior; Suicidal behavior -- Treatment; Teenagers -- Suicidal behavior; Youth -- Suicidal behavior; Play therapy; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Suicide